Utilização de polpa cítrica desidratada na alimentação de coelhos em crescimento - Maria, Bruno Giovany de (2008)
Two experiments have been carried out to determine the digestibility coefficient and nutritive value of dehydrated citrus pulp (DCP) for rabbits, and also to assess the viability of DCP usage in different replacement levels of digestible energy of corn, during the growing phase. In the digestibility assay, 30 White New Zealand rabbits with 45 days old were used, distributed in a completely randomized design, receiving two diets, being one reference diet, and another one a test diet, in which the DCP replaced 20% of the reference diet on dry matter, using 15 replications per treatment. The assay lasted 14 days, being 10 days of this period for adaptation and 4 days for feces collection. The apparent digestible coefficient of DM, CP, NDF, ADF and CE of DCP were, respectively, 83.75; 70.12; 40.14; 68.98; and 81.48% and the total digestible values were, respectively, 76.04; 5.03; 9.52; 15.09%; and 3394 kcalED/kg DM. In order to evaluate the performance of growing rabbits, 120 White New Zealand rabbits were used, from 32 to 70 days old, distributed in a completely randomized block design, with six treatments, being one reference ration with no DCP and another five rations with the DCP included, replacing the digestible energy of corn in 20, 40, 60, 80, and 100%, with 10 replications per treatment and two animals per experimental unit. In the period from 32 to 50 days old, the gradual increase of DCP use resulted in a reduction on the daily feed intake in a linear way (DFI), on daily weight gain (DWG) and on live weight at 50 days (LW50) of age. Quadratic effects on the feed conversion (FC) and on the ration costs/kg of live weight gain (Cost) resulted in better values, with 42.74 and 43.33% of corn replacement for DCP, respectively. Applying the Dunnet test, the replacement of 20% corn's DE for DCP was the only one that did not present loss in relation to the reference ration on DFI, DWG and LW50, while significant impairments on FC and Cost were only observed when the DCP completely replaced the corn's DE. From 32 to 70 days old, increase in DCP levels in replacement of corn's DE impaired linearly the DFI and DWG. However, quadratic effects on the FC and Cost presented better results with 44.40 and 45.30% of corn's DE replacement, respectively. Except for the 20% corn's DE replacement, all of the others presented worst results in relation to the reference ration for DFI and DWG. However, only the total replacement of corn for DCP caused a negative impact on FC and Cost. The gradual increase of DCP use linearly reduced the carcass weight and commercial cuts weight. Applying the Dunnet test, the diets with levels above 40% of corn's DE replacement for DCP presented worst results than the reference ration for posterior limbs weight, loin, thorax-cervix part and head. When 20%, or more, of corn's DE were replaced with DCP, the carcass and the limbs weight presented lower values. There was a linear reduction on the carcass yield (CY), loin (LY) and thorax-cervix part (TCY), and a enhance on the anterior (ALY) and posteriors (PLY) limbs and on the head (HeY) when DCP increased in rations. When compared to the reference ration, the worst results of CY, ALY, PLY, LY, HeY were verified in diets that presented levels at 40; 100; 40; 100; and 60% up, respectively, of corn's DE replacement for DCP. No significant difference was noticed for TCY. Based on the experiment results it is possible to conclude that, even though DCP has a high nutritive value, it needs to be used with caution, allowing replacing the corn up to 20% in growing rabbits diets.